Total Hip Arthroplasty Using a Polished Tapered Cemented Stem in Hereditary Multiple Exostosis. (5th April 2016) - Kanda, Akio; Kaneko, Kazuo; Obayashi, Osamu; Mogami, Atsuhiko
Abstract : A 61-year-old Japanese man underwent right total hip arthroplasty for hereditary multiple exostosis. At first presentation, he had suffered from coxalgia for a long time. On radiographic images, there was a gigantic femoral head, increased shaft angle, and large diameter of the femoral neck. He had also developed coxarthrosis and severe pain of the hip joint. The transformation of the proximal femur bone causes difficulty in setting a cementless total hip prosthesis. Therefore, total hip arthroplasty using a cemented polished tapered stem was performed via a direct lateral approach. Using a cemented polished tapered stem allowed us to deal with the femoral bone transformation and bone substance defectiveness due to exostosis and also minimized the invasiveness of the operation.